2016
DOI: 10.1038/srep36058
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulatory effects of offline low-frequency repetitive transcranial magnetic stimulation of the motor cortex: A functional magnetic resonance imaging study

Abstract: Repetitive transcranial magnetic stimulation (rTMS) of the primary motor cortex (M1) can modulate cortical excitability and is thought to influence activity in other brain areas. In this study, we investigated the anatomical and functional effects of rTMS of M1 and the time course of after-effects from a 1-Hz subthreshold rTMS to M1. Using an “offline” functional magnetic resonance imaging (fMRI)-rTMS paradigm, neural activation was mapped during simple finger movements after 1-Hz rTMS over the left M1 in a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Numerous investigations have proved that the aberrant spontaneous neural activity and functional networks of several diseases could be modulated by using repetitive transcranial magnetic stimulation (rTMS) through changing the excitability of the site of stimulation as well as the distant anatomically connected sites [16][17][18][19][20][21][22]. Previous rTMS studies on patients with cognition impairment in Alzheimer's disease, Parkinson's disease, schizophrenia, and dementia in older patients have reported significant positive effectiveness on improving cognitive ability [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigations have proved that the aberrant spontaneous neural activity and functional networks of several diseases could be modulated by using repetitive transcranial magnetic stimulation (rTMS) through changing the excitability of the site of stimulation as well as the distant anatomically connected sites [16][17][18][19][20][21][22]. Previous rTMS studies on patients with cognition impairment in Alzheimer's disease, Parkinson's disease, schizophrenia, and dementia in older patients have reported significant positive effectiveness on improving cognitive ability [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Using 50-Hz bursts of TMS (e.g., cTBS), decreased cortical excitability was reported lasting up to 60 min ( Huang et al, 2005 ). In addition, 1-Hz rTMS decreased cortical inhibition up to 30 min following the cessation of TMS ( Muellbacher et al, 2000 ; Gerschlager et al, 2001 ), which was also shown by a decreased fMRI neural activity for up to 20 min ( Min et al, 2016 ).…”
Section: Short- and Long-term Effects Of Nibs On Cortical Excitabilitmentioning
confidence: 88%
“…These results could be related to individual clinical applications and mechanisms. Recent studies have indicated that with LF-rTMS (1 Hz) stimulation of the contralateral cerebral M1 area, the vicinal cortical activity signal decreased, inhibiting the stimulated cerebral cortex activation, and this stimulated effect can last for 20 minutes after treatment [46]. Some experimental studies have shown that 1 Hz LF-rTMS can increase action potential and excitatory postsynaptic current in hippocampal CA1 neurons, which inhibit cortical excitability [47].…”
Section: Discussionmentioning
confidence: 99%